2008
DOI: 10.1007/s10529-008-9721-6
|View full text |Cite
|
Sign up to set email alerts
|

Solid-liquid two-phase partitioning bioreactors for the treatment of gas-phase volatile organic carbons (VOCs) by a microbial consortium

Abstract: A two-phase partitioning bioreactor (TPPB), employing styrene-butadiene co-polymer beads as the sequestering/delivery phase, was used to treat high step change loadings of toluene in a contaminated air stream. The polymers, which are biocompatible and non-bioavailable, allowed the use of a microbial consortium and effectively absorbed and released the toluene vapours for biodegradation, while providing a buffering effect against high toluene transients. Toluene loadings were increased from a base steady state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…biofilm) could adversely affect the adsorption capacity of them as packing materials in the biofilter, although Nabatilan and Moe (2010) observed that the adsorption capacity of a GAC prefilter was not significantly affected with humidity values lower than 90%. In addition, the partition coefficient values obtained in this work are in agreement with those previously reported for sorption into rubber of aqueous phase toluene and m-xylene (Daugulis and Boudreau, 2008;Gunasekara et al, 2000;Kim et al, 1997). …”
Section: Equilibrium Adsorption Experimentssupporting
confidence: 91%
“…biofilm) could adversely affect the adsorption capacity of them as packing materials in the biofilter, although Nabatilan and Moe (2010) observed that the adsorption capacity of a GAC prefilter was not significantly affected with humidity values lower than 90%. In addition, the partition coefficient values obtained in this work are in agreement with those previously reported for sorption into rubber of aqueous phase toluene and m-xylene (Daugulis and Boudreau, 2008;Gunasekara et al, 2000;Kim et al, 1997). …”
Section: Equilibrium Adsorption Experimentssupporting
confidence: 91%
“…Nevertheless, silicone oil has certain drawbacks as transfer vector, as it is relatively expensive and its recovery may increase process costs. Alternative organic phases, including solid polymers, have been proposed for the degradation of poorly soluble compounds [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al ( 2005 ) had shown earlier that, for a pure strain of bacteria treating VOCs, a constant biomass concentration will eventually be established due to cellular maintenance requirements, which are responsible for all of the substrate consumed. This principle can be extended to mixed microbial consortia present in the reactor, after an initial growth period (Daugulis and Boudreau 2008 ) . …”
Section: Biomass Concentrationmentioning
confidence: 99%
“…Nevertheless, silicone oil has certain disadvantages such as its relatively high cost and because its recovery may increase process costs. Recently, it has been proposed that solid polymers could be used as an alternative organic-phase, for the degradation of hydrophobic compounds (Daugulis and Boudreau 2008 ) .…”
Section: Solubility Of the Pollutantmentioning
confidence: 99%
See 1 more Smart Citation